Optimized White Reflectance in Photonic‐Network Structures. Issue 18 (23rd May 2019) - Utel, Francesco; Cortese, Lorenzo; Wiersma, Diederik S.; Pattelli, Lorenzo
Abstract: 3D disordered networks are receiving increasing attention as they represent a versatile architecture for highly scattering materials. However, due to their complex morphology, little is known about the interplay between their structural and optical properties. A simple algorithm that allows for the generation of photonic‐network structures inspired by that of the Cyphochilus beetle, famous for the bright‐white reflectance of its thin cuticular scales, is described. This model allows the degree of structural anisotropy and filling fraction of the network to be varied independently, revealing the key contribution of these two parameters to the overall scattering efficiency. Rigorous numerical simulations show that structures obtained with the use of this algorithm can exceed the broadband reflectance of the beetle while using less material, providing new insight into the design of advanced scattering materials. Abstract : Despite their outstanding efficiency as broadband diffusers, the complexity of 3D random‐network materials hinders understanding of the interplay between their structural and optical properties. The key role of anisotropy and volume fraction in this relationship is demonstrated through the use of rigorous simulations and a simple generative algorithm that allows for the design of lightweight structures with tailored scattering strength.